Polis, Loimos, Stasis: Thucydides about Disintegration of the Political System - Mirjana Stefanovski; Kosta Čavoški (Conatus - Journal of Philosophy, 2023)
This paper discusses Thucydides’ analysis of the disintegration of the political community under the unbearable stress in cases of the plague epidemic in Athens and civil war in Kerkyra. Due attention is paid to Thucydides’ methodology: the application of the art of medicine and antilogies. The destruction of the morality, fading away of virtue and neglect of both human and divine laws caused by the enormous fear of plague are presented through contrasting the state of lawlessness to the picture of the ideal order from the famous Pericles’ speech in honor of the fallen Athenians. It is being analyzed marked similarity between the state of lawlessness in Athens and the destruction of the political order in stasis in Kerkyra concerning the destruction of the public morality, disappearing of lawfulness, and cancelling of the common good, despite the difference in predominant motivating passions – fear and lust for power, and different ways of corruption of the order in polis – apolitical stance and apathy vs. radical politicization. Finally, it is underlined Thucydides’ understanding of repetition of the historical events after the same pattern because of the changelessness of human nature. It is milder in peace and regular ordered state of affairs, so that people are usually sensible and honest, acquire moral stance and embrace lawfulness, whereas when it is exposed to danger and faces the hardest challenges, it loses its considerations and restraints and shows its evil, violent and cruel side.